1993
DOI: 10.1128/aem.59.6.1893-1897.1993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Oxygen Concentration on Diacetyl and Acetoin Production by Lactococcus lactis subsp. lactis biovar diacetylactis

Abstract: The production of aroma compounds (acetoin and diacetyl) in fresh unripened cheese by Lactococcus lactis subsp. lactis biovar diacetylactis CNRZ 483 was studied at 30°C at different initial oxygen concentrations (0, 21, 50, and 100% of the medium saturation by oxygen). Regardless of the initial 02 concentration, maximal production of these compounds was reached only after all the citrate was consumed. Diacetyl and acetoin production was 0.01 and 2.4 mM, respectively, at 0% oxygen. Maximum acetoin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Boumerdassi et al (1996) confirmed that oxygen increases NADH oxidase activity (Condon, 1987), which causes NADH reoxidation to the detriment of activities of lactate de- Table 2. Evolution of average amounts of the aroma compounds quantified in the headspace of the yogurts made under the different oxidoreduction potential (Eh) conditions during 28 d of storage 1 hydrogenase, butanediol dehydrogenase, and acetoin dehydrogenase (Bassit et al, 1993). Then, excess pyruvate is eliminated partially through acetolactate production, which increases production of diacetyl (Boumerdassi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Boumerdassi et al (1996) confirmed that oxygen increases NADH oxidase activity (Condon, 1987), which causes NADH reoxidation to the detriment of activities of lactate de- Table 2. Evolution of average amounts of the aroma compounds quantified in the headspace of the yogurts made under the different oxidoreduction potential (Eh) conditions during 28 d of storage 1 hydrogenase, butanediol dehydrogenase, and acetoin dehydrogenase (Bassit et al, 1993). Then, excess pyruvate is eliminated partially through acetolactate production, which increases production of diacetyl (Boumerdassi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…AL and diacetyl plus acetoin were assayed as described previously (17,29,30). Diacetyl alone was measured after distillation (1). Lactose, citrate, lactate, acetate, formate, ethanol, pyruvate, and butanediol production was determined by high-performance liquid chromatography with an HPX-78P anion-exchange column (Bio-Rad, Inc.) with 0.01 NH 2 SO 4 as the elution fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Diacetyl is a flavor compound essential in many dairy products such as butter, cream, and some cheeses. Its production was shown to depend on the strains used as starter cultures (9) and the conditions of fermentation such as pH, oxygen, and temperature (1,4,12). Although changing the conditions of fermentation can lead to a very significant increase in diacetyl concentration, it is sometimes impossible to apply optimal conditions in actual factory processes.…”
mentioning
confidence: 99%
“…Under aerobiosis, however, the situation is somewhat different because an additional enzyme, NOX, is also involved. Water-forming NOX, encoded by the noxE gene, catalyzes the oxidation of NADH to NAD + at the expense of oxygen, which is reduced to H2O [14,20]. Therefore, in the presence of oxygen, NOX competes with LDH for NADH, resulting in a decrease in the NADH/NAD + ratio and, consequently, in a lower LDH activity.…”
Section: Isolation Of Mutant Strains Overproducing Acetoinmentioning
confidence: 99%